An Elderly Employment Model For The Thai Automotive Industry - Sadangharn, Pornrat (The South East Asian Journal of Management, 2017)
This research aims at studying an elderly employment model for the Thai automotive industry. Mixed methods with a sequential exploratory strategy were utilized. Grounded theory was employed by using in-depth interviews to investigate the characteristics of elderly employment in the Thai automotive industry. For this stage of the research, theoretical and purposive sampling was used to select 32 key informants from four groups of stakeholders: (1) elderly workers, (2) employers or human resource managers, (3) government officers, and (4) academics. The findings were then validated using a quantitative approach with structural equation modelling (SEM). A total of 308 elderly workers and human resource managers were surveyed regarding their opinion about elderly employment. Based on the survey, the elderly employment model in the Thai automotive industry, which is comprised of the approach to elderly employment, elderly employment preparation, and key success factors for elderly employment, was revealed to be a good fit.